What is not translable of Elsa Morante’s Storia in the Spain of 1976. - Guidotti, Gloria (Cuadernos de Filología Italiana, 2004)
Although in 1976 the publishing house Plaza y Janés had signed with Elsa Morante a «precise and inescapable compromise» to guarantee an «absolutely accurate and complete» translation of her novel La Storia, however, according to what the author wrote, the text had been «arbitrarily altered and several passages suppressed, especially those which could, in the publishers’ opinion, upset the then current political system of Spain». Was it a publishing initiative by Plaza y Janés to obtain the nulla osta, or are these modifications due to a kind of censorship or, even, of self-censorship of the translator himself? We could speak —concerning the Spain of 1976— of a strict control over Morante’s text, of a rigorous supervision regarding the free and uncontrolled spread of ideas.